2013
DOI: 10.1155/2013/785025
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitudes of Physicians and Nurses about Violence against Women

Abstract: Cross-sectional study compares the perception and attitudes about violence against women of physicians and nurses working in the primary health care clinics in Ribeirão Preto, SP. A total of 170 physicians and 51 nurses were interviewed in the District Health Clinics. Physicians feel more comfortable than nurses to talk about the sex life of patients (P = 0.048) and to investigate the use of drugs (0.001). Compared to the nurses greater number of physicians believed that the aggression to the woman by the husb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…A discomfort feeling in receiving and listening to the abused women persists, as, ultimately highlighted by other studies (Lazenbatt & Thompson-Cree 2009, Ramsay et al 2012, Baraldi et al 2013.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A discomfort feeling in receiving and listening to the abused women persists, as, ultimately highlighted by other studies (Lazenbatt & Thompson-Cree 2009, Ramsay et al 2012, Baraldi et al 2013.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies indicated the presence, among operators, of the frequent stereotype of the battered woman. She is considered partially responsible for her situation of abuse (Lazenbatt et al 2005, Baraldi et al 2013, Taylor et al 2013, she has facilitated in any manner the violent episode, and she has voluntarily chosen violent partners or to live in situations of abuse (Shadigian & Bauer 2004, Marinheiro et al 2006, Baraldi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las enfermeras tienen un nivel medio de conocimiento18, 21, y aunque la mitad afirman conocer el protocolo, dato ligeramente superior a otros estudios18, 21, 22, solo lo aplicaron un 34%; la detección de la VG parece basarse más en las propias percepciones que en el uso de los protocolos 19 . Además, aunque consideran que la VG atañe a todos los profesionales y que la víctima pasa desapercibida18, 21, el nivel de detección encontrado ha sido insuficiente23, 24, 25, 26, 27; se ha visto una escasa actitud expectante ante el diagnóstico16, 18 y en el planteamiento del diagnóstico diferencial ante lesiones físicas6, 17, 18, 21. Esta pasividad explicaría por qué, muchas veces, no se identifica el problema a partir de los síntomas inespecíficos o lesiones de la víctima 23 .…”
Section: Discussionunclassified
“…Algunos trabajos indican que entre un 29% y un 40% de las enfermeras en AP se sienten incómodas preguntando a los pacientes sobre este tema6, 16. En Asturias, aunque existe un Registro de Atención Sanitaria en Violencia contra las Mujeres del Principado de Asturias (VIMPA), en menos del 10% de las historias es posible identificar de forma automática si ha habido violencia; esto se atribuye a la falta de habilidades en el uso de la herramienta informática y a la escasa formación sobre VG 14 .…”
Section: Introductionunclassified